A STUDY ON THE EFFECT OF BENEFITS AND SACRIFICES FACTORS OF E-COMMERCE PAID MEMBERSHIP ON THE PERCEIVED VALUE AND INTENTION TO CONTINUE USING E-COMMERCE - Park, Soeon (PEOPLE: International Journal of Social Sciences, 2024)
In this study, we apply VAM to explore the benefits and sacrifice factors associated with paid membership in domestic e-commerce and investigate the impact on perceived value and users' intention to continue using e-commerce. Additionally, this study assesses whether the impact of these factors on perceived value varies by membership type. Perceived benefit factors for paid e-commerce members include differentiation, enjoyment, sharing, point benefit, discount benefit, content benefit, and delivery benefit. Perceived sacrifices include fee, complexity, and lost opportunity. In the case of Coupang Rocket Wow, discount benefit, delivery benefit, and opportunity loss have a significant impact on perceived value. In the case of Naver Plus membership, discount benefit, point benefit, and fee were found to have a significant impact on perceived value. The perceived value of Coupang Rocket Wow and Naver Plus membership has a positive effect on the intention to continue using Coupang and Naver. Additionally, it was found that there was a significant difference in the impact of opportunity loss on perceived value between Coupang Rocket Wow and Naver Plus Memberships